2008
DOI: 10.1002/pmic.200700560
|View full text |Cite
|
Sign up to set email alerts
|

SsrA genes of streptomycetes and association of proteins to the tmRNA during development and cellular differentiation

Abstract: Transfer-messenger RNA (tmRNA, 10Sa RNA, ssrA) is bacterial RNA having both tRNA and mRNA properties and playing an essential role in recycling of 70S ribosomes that are stalled on defective mRNA. The trans-translational system is thought to play a crucial role in bacterial survival under adverse conditions. Streptomycetes are Gram-positive soil bacteria exposed to various physical and chemical stresses that activate specialized responses such as synthesis of antibiotics and morphological differentiation. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…A highly intriguing feature of the tmRNA system is that its function has been adapted to fulfil the specific physiological needs of various bacterial species. Studies of tmRNA in several distinct bacterial species (Withey and Friedman, 1999;Keiler and Shapiro, 2003;Shin and Price, 2007;Abe et al, 2008;Keiler, 2008;Mikulik et al, 2008;Thibonnier et al, 2008;Ujiie et al, 2009;Okan et al, 2010) have yielded new and unique insights into the structure, function and diverse physiological roles played by this system. Our studies of the tmRNA system in F. tularensis demonstrate that this small-genome bacterium has an active trans-translation system that is important for normal growth, resistance to a variety of stress conditions and virulence of the pathogen in a mouse model of tularemia.…”
Section: Introductionmentioning
confidence: 99%
“…A highly intriguing feature of the tmRNA system is that its function has been adapted to fulfil the specific physiological needs of various bacterial species. Studies of tmRNA in several distinct bacterial species (Withey and Friedman, 1999;Keiler and Shapiro, 2003;Shin and Price, 2007;Abe et al, 2008;Keiler, 2008;Mikulik et al, 2008;Thibonnier et al, 2008;Ujiie et al, 2009;Okan et al, 2010) have yielded new and unique insights into the structure, function and diverse physiological roles played by this system. Our studies of the tmRNA system in F. tularensis demonstrate that this small-genome bacterium has an active trans-translation system that is important for normal growth, resistance to a variety of stress conditions and virulence of the pathogen in a mouse model of tularemia.…”
Section: Introductionmentioning
confidence: 99%
“…, 2005). In experiments with S. aureofaciens, we found that the highest level of SmpB was in the cells from exponential phase of growth and a descending amount in the cells from stationary phase (Mikulík et al. , 2008), which indicates that availability of the SmpB can be involved in regulation of tmRNA stability.…”
Section: Discussionmentioning
confidence: 88%
“…In experiments with S. aureofaciens, we found that the highest level of SmpB was in the cells from exponential phase of growth and a descending amount in the cells from stationary phase (Mikulík et al, 2008), which indicates that availability of the SmpB can be involved in regulation of tmRNA stability. A previous study demonstrated that antibiotics causing amino acid misreading (kanamycin, streptomycin, hygromycin B, paromomycin and gentamicin) induce read-through of stop codons and enhance the tmRNA mediated protein tagging.…”
Section: A B C Dmentioning
confidence: 82%
See 1 more Smart Citation
“…Compared to the synthesis of regulatory proteins, less energy is needed for the synthesis of a small RNA (sRNA) [55]. Among the ncRNAs detected in the genome, riboswitches (elements that control expression in response to various metabolites and can function as sensors or binding sites for a receptor protein that senses a change in the cellular environment) were identified through the analysis of active transcripts.…”
Section: Resultsmentioning
confidence: 99%